2015
DOI: 10.1088/0957-4484/27/2/025303
|View full text |Cite
|
Sign up to set email alerts
|

Regularly patterned multi-section GaN nanorod arrays grown with a pulsed growth technique

Abstract: The growth of regularly patterned multi-section GaN nanorod (NR) arrays based on a pulsed growth technique with metalorganic chemical vapor deposition is demonstrated. Such an NR with multiple sections of different cross-sectional sizes is formed by tapering a uniform cross section to another through stepwise decreasing of the Ga supply duration to reduce the size of the catalytic Ga droplet. Contrast line structures are observed in either a scanning electron microscopy or transmission electron microscopy imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…No (11̅01) plane was observed in the GaN NWs. Lin et al and Jung et al studied the effects of the pulse duration and the interruption time on the GaN NW growth and found both parameters are crucial to limit the lateral growth and enhance the growth in axial direction. , Zhang et al and Tu et al observed the Ga droplet formation at the NW top after the Ga precursor pulse and the Ga droplet size can be controlled by tuning the supply of the Ga precursor. , In this way, GaN NWs with multiple sections of different cross-sectional sizes were formed and multiple color emissions from single NWs were realized with different InGaN QW growth on different sections …”
Section: Iii-nitride Nanowire Materials and Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…No (11̅01) plane was observed in the GaN NWs. Lin et al and Jung et al studied the effects of the pulse duration and the interruption time on the GaN NW growth and found both parameters are crucial to limit the lateral growth and enhance the growth in axial direction. , Zhang et al and Tu et al observed the Ga droplet formation at the NW top after the Ga precursor pulse and the Ga droplet size can be controlled by tuning the supply of the Ga precursor. , In this way, GaN NWs with multiple sections of different cross-sectional sizes were formed and multiple color emissions from single NWs were realized with different InGaN QW growth on different sections …”
Section: Iii-nitride Nanowire Materials and Devicesmentioning
confidence: 99%
“…537 To avoid the growth in the pyramid shape, pulsed growth mode had to be and the Ga droplet size can be controlled by tuning the supply of the Ga precursor. 540,541 In this way, GaN NWs with multiple sections of different cross-sectional sizes were formed and multiple color emissions from single NWs were realized with different InGaN QW growth on different sections. 541 We also worked on the Ga-polar GaN NW growth by selective area MOVPE, but we investigated the growth with continuous flows of Ga precursor and NH 3 to seek possibilities for the growth to take the vertical NW shape.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Figure 10c shows the nanowires grown with an additional temperature variation step, which leads to two segment pairs of “wide-narrow-wide” diameter configurations. In previous works, researchers found that the diameters of ZnO or GaN can be changed by controlling the source supply [37,58]. In this work, a new method to control the nanowire diameter is demonstrated, which is instructive with respect to the diameter-controlled growing nanowires of other materials.…”
Section: Resultsmentioning
confidence: 87%
“…It should be mentioned that for the selective area growth (SAG) of NWs, parasitic deposition on the SiO 2 surface can also be eliminated without using trenches. In other words, the trench is not indispensable for eliminating the parasitic deposition in SAG.…”
mentioning
confidence: 99%